Comparison of Low Birth Weight Incidence Between the Program and Non-Program of the First 1000 Days of Life - Muhammad Yusuf Izzati; Andi Tihardimanto; Najamuddin (Jurnal Multidisiplin Madani, 2023)
Currently, Indonesia is facing a challenge regarding the issue of low birth weight (LBW) infants, including in South Sulawesi, which contributes to infant mortality. Data shows an increasing incidence of LBW in South Sulawesi from 2.94% in 2013 to 8.13% in 2015. This article also discusses the First 1000 Days of Life (HPK) program as an effort to improve maternal and child health in Indonesia. The research conducted is a descriptive survey using a cross-sectional study design. The research sample consists of pregnant mothers who participate in the First 1000 Days of Life program and those who do not participate in the program in the city of Makassar. The objective of this study is to determine the incidence of LBW among program participants and non-participants of the First 1000 Days of Life program at PSPD UINAM in the city of Makassar. Research findings: The incidence of LBW among active program participants is lower, with a total of 1 (4%) out of 26 infants, compared to a higher incidence of LBW among non-program participants, with a total of 8 infants (31%) out of 26 infants. Conclusion: The incidence of LBW in the city of Makassar is higher among pregnant mothers who do not participate in the program compared to those who do participate